Interactive Cinematic Experience Design and User Behavior Analysis Enabled by Mobile Augmented Reality - Wang, Fangzhao (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rapid advancement of mobile augmented reality (MAR) technology and its deep integration into the cultural and entertainment sectors, the traditional model of film viewing is undergoing a paradigm shift from passive reception to interactive engagement. The growing demand for immersive and participatory cinematic experiences has catalyzed the convergence of the film industry with MAR technologies. However, existing research on MAR-based interactive film scenes remains constrained by insufficient capture of real-time user interactions and a superficial understanding of underlying psychological mechanisms. This study focuses on the design of interactive experiences within film scenes enhanced by MAR and addresses two core areas. First, a method for generating interactive film scenes was proposed, integrating semantic alignment between virtual elements and real-world environments, interactive logic structuring, and immersion optimization to achieve spatially dynamic and interactive cinematic representations. Second, through the application of eye-tracking and behavioral log analysis, user behavioral patterns during interaction were investigated, with the aim of mapping these behaviors to their corresponding psychological needs. The study is intended to overcome the methodological limitations of prior research, offering a theoretical foundation for the precise design of MAR-based cinematic interaction environments. Additionally, it provides practical insights for the development of interactive film products, aiming to enhance user satisfaction and promote a paradigm innovation in cinematic interaction research through a “technology + art” integrated perspective.